Efficient and Stable Antimony Selenoiodide Solar Cells. Issue 8 (9th February 2021) - Nie, Riming; Hu, Manman; Risqi, Andi Muhammad; Li, Zhongping; Seok, Sang Il
Abstract: Although antimony selenoiodide (SbSeI) exhibits a suitable bandgap as well as interesting physicochemical properties, it has not been applied to solar cells. Here the fabrication of SbSeI solar cells is reported for the first time using multiple spin‐coating cycles of SbI3 solutions on Sb2 Se3 thin layer, which is formed by thermal decomposition after depositing a single‐source precursor solution. The performance exhibits a short‐circuit current density of 14.8 mA cm −2, an open‐circuit voltage of 473.0 mV, and a fill factor of 58.7%, yielding a power conversion efficiency (PCE) of 4.1% under standard air mass 1.5 global (AM 1.5 G, 100 mW cm −2 ). The cells retain ≈90.0% of the initial PCE even after illuminating under AM 1.5G (100 mW cm −2 ) for 2321 min. Here, a new approach is provided for combining selenide and iodide as anions, to fabricate highly efficient, highly stable, green, and low‐cost solar cells. Abstract : The fabrication of SbSeI solar cells using multiple spin‐coating cycles of SbI3 solutions on Sb2 Se3 thin layer (deposited by using a single‐source precursor solution) is reported. The champion cell exhibits a power conversion efficiency of 4.10% under standard air mass 1.5 global (100 mW cm −2 ). These cells show good humidity, photo‐, and thermal stabilities.